ANALISIS STRATEGI PEMASARAN PADA USAHA BATIK TANAH LIEK BUNDO KANDUANG - Yunita Larasati; Rose Rahmidani (Jurnal Ecogen, 2019)
The purpose of this study was to determine the marketing strategies used by the Batik Tanah Liek Bundo Kanduang business in the city of Padang, West Sumatra. This research method is descriptive qualitative. The study was conducted using purposive sampling techniques as for the source and several key informants through the results of in-depth interviews or in-depth interviews and direct observations to the object of the researcher. Secondary data supporting this research were obtained from documents available at the research object. To test the validity of the data used source triangulation.Based on information from the informants of this study it can be explained that the overall marketing strategy is less than optimal and there are still obstacles to the marketing strategy used by the Batik Tanah Liek Bundo Kanduang business. As for some of the problems experienced by the Batik Tanah Liek Bundo Kanduang business which caused suboptimal marketing strategies carried out both from the product, price, promotion and location. As for the description of the problems that exist in the business, namely: 1) The lack of reliable human resources in terms of making batik, 2) Lack of attention from local governments in order to develop SMEs, especially batik liek, 3) There are still a small number of followers on social media instagram created by Batik Tanah Liek Bundo Kanduang business, 4) Lack of promotion by the Batik Tanah Liek Bundo Kanduang business because the business focused on personal selling, 5) Lack of strategic location and the need for innovative store display.Based on research the researchers conducted a recommendation that the writer could suggest to the Tanah Liek Bundo Kanduang Batik business, namely to use marketing methods such as: advertising newspapers, banners, and placing their products at the center of souvenirs scattered in West Sumatra and further intensifying promotions in the media social which is now widely used by people in all walks of life such as Instagram, Facebook, making the web and so on.Keywords: marketing strategic, batik tanah liek.